Students’ Communicative Competence: A Descriptive Study In English Education Program At Stkip Taman Siswa Bima - Sholihin, Sholihin (STKIP Taman Siswa Bima, 2021)
The purpose of this research are: (1) To describe the students communicative competence. (2) To describe the factors that affects their communicative competence. This study investigates how well the students do in using English to communicate with others with the help of recording and interview questions which may help the writer to find out the students weakness in sociolinguistic competence and to find out the factors that influence it in English Education program’s students. This research is descriptive research, in descriptive research the writer analyzed and presented the fact systematically therefore it could be understood and concluded easily. Type of this research is qualitative research. This research used the primary source was taken from the students’ utterances recording in English Education Program’s of STKIP Taman Siswa Bima. The secondary data is taken from many communicative competence’ journals that related with this research and also the data is taken from internet website. The result of this research showed that there were some students’ weakness in sociolinguistic competence and some factors that influences it. The students’ weakness in sociolinguistic competence found are 7, as follows: Age was appear in Data 2, Gender was appear in Data 5 and 6, Social Status was appear in Data 1 and Impoliteness in communication was appear in Data 3, 4 and 7. Besides, some causes for the students’ weakness in sociolinguistic competence found are 6, as follows: Students prefer to use their Mother Tongue, they cannot make good use of the opportunities for practice their sociolinguistic competence, the students are afraid of loser face when making mistakes. The students’ sociolinguistic competences are also influenced by their social and culture. The last is influenced by films or movies.